Keanekaragaman Vegetasi Mangrove di Kawasan Hutan Mangrove Taman Nasional Karimunjawa, Kabupaten Jepara, Jawa Tengah - Roni Sipayung (Wana Lestari, 2023)
This study aims to determine the density of mangrove vegetation found in mangrove forest areas. This research was conducted in the Mangrove Forest Area of ​​Karimunjawa National Park, Jepara Regency, Central Java. Retrieval of research data using a systematic path with a total of 75 plots in the entire Mangrove Forest Area of ​​Karimunjawa National Park with nested sampling method. Using this method, the number of species and vegetation density values ​​were obtained in the form of seedling density, sapling density, and tree density. Data analysis used quantitative description in the form of a graph of mangrove vegetation density. The results showed that the density of vegetation in the Mangrove Area of ​​Karimunjawa National Park, Jepara Regency, Central Java was classified as moderate. The vegetation density values ​​for block A at the growth rate of seedlings, saplings and trees were 13103.45 individuals/ha, 2096.55 individuals/ha and 331.03 individuals/ha while the density of mangrove vegetation for block B at the growth rate of seedlings, saplings, and trees respectively, namely 23478.26 individuals/ha, 3756.52 individuals/ha, and 217.39 individuals/ha.The diversity index value in block A was 1.797 while in block B it was 2.110.